Lessons learnt from tsunami: conflicts arising from aid distribution - Dissanayake, Lakshman (My University, 2006)
According to the information available, thirteen coastal districts were devastated by 2004 tsunami disaster: 232,677 families were affected; 79,431 families were displaced; 500,666 persons were displaced; 161,684 were placed in temporary IDP camps; 30,000 were dead. Instantly, communities and local authorities responded quickly to address immediate needs of the affected people. Government released LKR 93 million from the National Treasury to facilitate relief operations in ten of the affected districts. In addition, a Centre for National Operations (CNO) was formed under the Presidential Secretariat to oversee and monitor emergency programs. Three new task forces comprising representatives of the public and private sectors were also formed under the Presidential Secretariat: Task Force for Rescue and Relief, Task Force to Rebuild the Nation and Task Force for Logistics and Law and Order. At the district level, Disaster Management Authorities were appointed to coordinate local relief efforts. Most importantly, the Government has been coordinating relief and recovery activities with the LTTE, which was providing people with temporary shelter, distributing food and other goods, and preparing plans for reconstruction. The LTTE also actively participated in District Level task Forces, and undertook its own needs assessment of the North East. Many community groups and NGOs provided food, health supplies and services, and water, and other basic necessities to thousands of families throughout the country. Several NGOs delivered aid to the tsunami-affected people in many parts of the country, while the Tamil Rehabilitation Organization (TRO) provided emergency assistance to the people especially in the North East. The response of the international community was also rapid. By January 6, contributions in cash and kind of around $22 million had been pledged by bilateral donors for post-tsunami relief programs, channeled mainly through national and international NGOs. Several have also pledged funds for relief and/or reconstruction efforts, including but not limited to the United States, Australia/The Australian Agency for International Development (AUSAID), Canada/the Canadian International Development Agency (CIDA), Germany, Japan, the European Union and the UK. The multilateral partners of Sri Lank, including the international financing institutions, have also responded quickly. On January 6, 2005 the UN launched a Flash Appeal aiming to raise $167 million for the immediate recovery of the country for the next six months; as of January 19, donations totaled @21.8 million. However, a greater part of the post-tsunami relief, reconstruction and rehabilitation (RRR) work in Sri Lanka has been carried out by government structures and international and local organizations with little emphisis on people’s participation. Information sharing between local communities and recovery agents is vital to ensure the success and sustainability of the tsunami recovery process. The relief process has failed to use participatory approaches. An assessment made by the World Bank, ADB and JBIC states that post-tsunami recovery should be guided by identified needs and local priorities and characterized by better communication and transparency in decision-making.
Keywords: Lessons learnt from tsunami: conflicts arising from aid distribution